Reforming the international financial system for development - Jomo K. S. (Jomo Kwame Sundaram) (Initiative for Policy Dialogue at Columbia (Series), 2010)
The 1944 Bretton Woods conference created new institutions for international economic governance. Though flawed, the system led to, a golden age in postwar reconstruction, sustained economic growth, job creation, and postcolonial development. Yet financial liberalization since the 1970s has involved deregulation and globalization, which have exacerbated instability, rather than sustained growth. In addition, the failure of Bretton Woods to provide a reserve currency enabled the dollar to fill the void, which has contributed to periodic, massive U.S. trade deficits.